THE EFFECT OF WORKLOAD AND BURNOUT ON NURSES' PERFORMANCE IN INTERNAL MEDICINE WARDS MEN AND WOMEN (Case Study at Jayapura Hospital) - Rosalina Cesilia; Kosasih; Ayu Laili Rahmiyati; Farida Yuliaty; Vip Paramarta; Fitriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study is expected to obtain empirical evidence on the effect of workload and Burnout on the performance of nurses in male and female internal medicine wards. The research methods used were verifiable descriptive analysis and multiple linear regression analysis. The number of respondents collected in this study was 53 people, representing all people who worked at Jayapura Hospital who were randomly selected. The results of the descriptive analysis showed that the influence of workload, Burnout and nurse performance in the male and female internal medicine ward was classified as a good criterion. The results of the study showed that both partially and simultaneously, workload and Burnout had a very significant influence on nurse performance, with a combined contribution of 93.1% to performance variation. This confirms that these two factors are dominant predictors that need to be managed strategically to maintain the quality of nursing services at referral hospitals.